The Efect Of Leverage, Growth, Market Value Added, and Macroeconomics On Stock Returns Mediated By Profitability - Yusefa, Helmi; Efni, Yulia; Kamaliah, Kamaliah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
The existence of an empirical phenomenon of an inconsistent relationship between stock returns and profitability, the inconsistency of macroeconomic influences with stock returns, and the inconsistency of previous research results on factors that affect stock returns are the main reasons behind this research, which questions whether DER, SG (MVA), inflation, and ROA affect stock returns and whether ROA is able to mediate the influence of DER, SG, MVA, and inflation on stock returns. The purpose of the study is to test and analyze whether DER, SG, MVA, inflation, and ROA affect stock returns and whether ROA is able to mediate the effect of DER, SG, MVA, and inflation on stock returns in the transportation and logistics sector listed on the IDX in 2018–2023. The sampling technique is a saturated sample; all populations are sampled. There are 8 companies that meet the qualifications in accordance with the specified population criteria. There are 79 samples from the 8 companies studied with the analysis method used, namely path analysis. At a significance level of 0.05 (5%), the results obtained show that DER, SG, inflation, and ROA have a direct effect on stock returns; MVA has no direct effect on stock returns. Profitability is able to mediate sales growth and MVA on stock returns, but it does not successfully mediate the influence between DER and inflation on stock returns.